50‐2: Research on adaptive voltage regulation algorithm on TFT‐LCD - Deng, Shijie; Wang, Qiang; Jin, Yufeng; Wu, Yu (SID International Symposium Digest of technical papers, 2024)
In the current global promotion of environmental protection and low‐carbon, to further reduce the power consumption of TFT‐ LCD, this paper proposes an algorithm based on image detection for adaptive adjustment of panel voltage and tests the algorithm on the monitor. The test results shows that the algorithm can achieve power reduction while maintaining image quality.